2017
DOI: 10.1177/0971521517697882
|View full text |Cite
|
Sign up to set email alerts
|

Editor’s Introduction: Gender and the Graphic

Abstract: Popular culture has the power to deliver political messages. This truism is never more evidenced in the contemporary era than in the case of comic books and graphic novels. From Maus through Citizen 13660, Radioactive Forever, The Ukrainian and Russian Notebooks, Bhimayana, Hush and March, the graphic novel, much more serious than 'comics', has been instrumental in raising the critical literacy level about events in history and present-day issues: the Holocaust, Japanese internment in the USA after Pearl Harbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Still, most importantly, it also tries to elevate the role of women and empower them through the use of graphic novels as a pedagogical tool in ESL classrooms. A number of studies are now looking into gender (mis) representations found in the narratives of graphic materials and have discovered both disturbing and hopeful observations when it comes to understanding gender or gender roles in society (e.g., Allison, 2014;Nayar, 2017), which findings and concerns are also shared by this study. By identifying and revealing what can be regarded as visual misrepresentations of or discrimination against women, it seeks to create awareness on these pertinent issues on both teachers and students in Malaysian contexts.…”
Section: Discussionmentioning
confidence: 67%
“…Still, most importantly, it also tries to elevate the role of women and empower them through the use of graphic novels as a pedagogical tool in ESL classrooms. A number of studies are now looking into gender (mis) representations found in the narratives of graphic materials and have discovered both disturbing and hopeful observations when it comes to understanding gender or gender roles in society (e.g., Allison, 2014;Nayar, 2017), which findings and concerns are also shared by this study. By identifying and revealing what can be regarded as visual misrepresentations of or discrimination against women, it seeks to create awareness on these pertinent issues on both teachers and students in Malaysian contexts.…”
Section: Discussionmentioning
confidence: 67%